Water Movement in Strawberry Beds - John R. Duval; Eric Simonne (EDIS)
An increasing concern for proper water usage and irrigation efficiency requires a better understanding of water movement in strawberry beds. The major factor that determines water movement in the soil is macro- and micro-pore space in the soil. This document is HS912, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date September 2003.